PENERAPAN PEMBERIAN HAK ASUH ANAK DIBAWAH UMUR OLEH ORANG TUA LAKI-LAKI DI PENGADILAN AGAMA PEKANBARU MENURUT INSTRUKSI PRESIDEN NOMOR 1 TAHUN 1991 TENTANG KOMPILASI HUKUM ISLAM - Ismina, Tria; Ismi, Hayatul; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In the household there must be a conflict that can be settled between the husband and wife wisely. This conflict can manifold appear as if the wife feels the husband is unable to meet the needs of his wife or the husband feels the wife can not perform his duties properly or because of other matters. Discuss the issue of divorce is certainly not much discussion of child custody. Often between men and women there is a struggle for child custody. But the provisions on custody of underage children will be under the care of his mother.Researchers want to study and answer the problem about how the application of custody of underage children by the parents of men according to Compilation of Islamic Law? What is the basis of judges' consideration in imposing custody of a child to a male parent based on Decision Number 0177 / Pdt.G / 2015 / PA.Pbr? Are the rights and obligations of the underage child already fulfilled by divorced parents?The method that writer use is method of sociological approach with collecting data as follows: literature study, document study, and interview.The results of research and discussion can be concluded that Here, custody of underage children who fall to the parents of men or father to look back kemaslahatan child and for good development in the child so as not to imitate his mother's behavior later. The judge considers that underage child custody may be to a male parent if, in the hearing, the man can provide the actual information that occurs during their marriage, such as the woman often abandons her child, does not care and does not caring for the child. Despite having been separated from the father of the child, the mother keeps paying attention in terms of education and gives affection and attention to his child, teaches and gains good knowledge.From the results of research problems there are three main things that can be concluded. First, the application of the provision of custody of underage children by the parents of men in the Religious Court of Pekanbaru according to the Compilation of Islamic Law determines that the child who has not determined that the child who has not mumayyiz or not yet 12 years is the right for the mother to maintain it, while if the child already mumayyiz, he can choose between his father or mother to act as the keeper. But there are several reasons that make the mother lose custody of her child even if still under age, can be because the mother does not care about her child under any circumstances, do not take care and keep her child as good as possible, do acts of violence and ignore all requirement of child. Secondly, from the data obtained by the author in the Religious Court of Pekanbaru, previously there was no decision that imposed the custody of the underage child to the male parents other than the verdict in Number 0177 / Pdt.G / 2015 / PA.Pbr. This is due to the judge's consideration in childcare and the seriousness of both parents in parenting. Suggestion, Parents who have broken up or divorced should still pay attention and provide affection without shortage to the child, especially the child is still under age who still need the attention of both parents.Keywords: Divorce-Child Rights-Compilation of Islamic Law